Perceptions of the COVID‐19 pandemic's impact on communities and wildlife trade: Preliminary qualitative analysis from hunters in Vietnam, Cambodia, and Laos. Issue 3 (8th February 2023) - Davis, Elizabeth Oneita; Castaneda, Marielle; Crudge, Brian; Lim, Thona; Roth, Vichet; Glikman, J. A.; Cao, Trung
Abstract: The COVID‐19 pandemic has accelerated efforts to engage critically with forest‐adjacent, rural, communities who rely on wildlife. We interviewed 109 hunters of wildlife across Vietnam, Cambodia, and Laos regarding the effect the COVID‐19 pandemic has had on them, as well as within their communities. We found that "negative economic impacts" was a prevalent theme due to loss of employment, rising prices, and restrictions on trade resulting from city‐wide lockdowns, factory closures, and border closures. In Vietnam, hunting was stated to have increased as young men returned to their villages; however, in Vietnam and Cambodia trade in wildlife was believed to have decreased due to the inability of middlemen traders to travel easily. Our results from Laos illustrated general economic cost, but otherwise no impact of COVID‐19 on hunting and trade in wildlife. Here, we show the complex impacts of a pandemic, with contextually specific conservation positives (such as decreased trade), and conservation negatives (such as increased hunting to supplement loss of employment). We illustrate the importance of establishing sustainable, non‐wildlife‐dependent livelihoods within rural communities, to mitigate hunting and the potential for disease transmission, and the value in engaging with hunters to understand locally and spatially specific trends in global conservation challenges. Abstract : In this qualitative study, we interviewed 109 hunters across Cambodia, Laos, and Vietnam, about the impact COVID‐19 had so far on them individually, as well as their communities. We found economic impacts to be cited across all three countries, which in Vietnam pushed some young men into hunting for the first time; however, border and city closures was also believed to have made the act of trade more challenging. Overall, our results illustrate the importance of engendering stability and sustainability within forest‐adjacent communities.